Variability in ciliary beat frequency in normal subjects and in patients with bronchiectasis. - Veale, D. (1993)
BACKGROUND--There is a wide variation in tracheobronchial clearance of inhaled aerosol in normal subjects and in patients with bronchiectasis, but little information is available on the variability in ciliary beat frequency (CBF). METHODS--The variability in CBF was measured in 10 nasal mucosal samples from each of 19 normal controls and 23 stable bronchiectatic subjects. RESULTS--The CBF varied at different mucosal sites in both normal subjects and bronchiectatic patients. Although the CBF of the fastest beating cilia was similar in both groups, the CBF of the slowest beating cilia was, on average, lower and showed greater within subject variation in bronchiectatic than in normal subjects. CONCLUSIONS--There is a wide variation in CBF in nasal mucosal samples and this is significantly wider in bronchiectatic subjects with some cilia beating slowly. This may be a consequence of chronic inflammation or infection.